THE IMPACT OF DIGITAL INFRASTRUCTURE ON ECONOMIC GROWTH: AN ECONOMETRIC ANALYSIS OF THE REGIONS OF UZBEKISTAN - Sanaqulova Aziza Amirovna (International Journal of Literature and Language Studies, 2026)
This article examines the role and significance of digital infrastructure in economic growth. In the context of the digital economy, the impact of internet penetration, information and communication technologies (ICT), and investments on economic development is analyzed from both theoretical and empirical perspectives. During the study, an econometric model was developed using data from the 14 regions of the Republic of Uzbekistan for the period 2015–2024. The results reveal that the level of internet usage and the volume of investments have a positive effect on the growth of Gross Regional Product (GRP). Furthermore, the findings indicate significant disparities in the development of digital infrastructure across regions. Based on the results, practical recommendations were proposed to enhance digital infrastructure, reduce interregional digital inequality, and accelerate economic growth.